Samoa : Financial Sector Assessment Program. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses key findings of the assessment of Banking Resolution, and Crisis Prevention and Management Frameworks for Samoa. It is recommended that the current regulatory framework to deal with financial institutions (FIs) should be reformed. The Central Bank of Samoa (CBS) has issued 'Prudential Statements" containing some prudential rules, ratios, and limits applicable to FIs, but there are no general standards for their enforcement, which is done on a purely discretional case-by-case basis. The powers from the Central Bank Act are not strong enough to enable the CBS to take enforcement actions. A fully amended legal and regulatory banking resolution framework is needed for the CBS to be able to deal effectively with serious banking problems.